The Relationship Between Human Resource Practices and Employee Retention in Small and Medium enterprises (SMEs) in Kenya - Mwangi, Emmanuel (Human Resource and Leadership Journal, 2026)
Purpose: The purpose of this article was to analyze the relationship between human resource practices and employee retention in small and medium enterprises (SMEs). Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The relationship between human resource practices and employee retention in SMEs highlights the significant role of training, compensation, and performance management in fostering employee loyalty. Studies show that effective HR practices such as career development opportunities and work-life balance policies positively influence employee satisfaction, reducing turnover intentions. SMEs that implement fair recruitment systems, provide adequate compensation, and offer growth opportunities experience higher retention rates and improved organizational performance. Unique Contribution to Theory, Practice and Policy: Social exchange theory, resource-based view (RBV) & herzberg’s two-factor theory may be used to anchor future studies on the relationship between human resource practices and employee retention in small and medium enterprises (SMEs). Compensation policies should be competitive yet sustainable, and SMEs should implement performance appraisal systems that emphasize development rather than just evaluation. Governments can incentivize SMEs to offer training grants and compensation tax relief to ease the financial burden of implementing retention‑enhancing HR practices.